PENDIDIKAN ANAK USIA DINI DALAM PERSPEKTIF AL-QUR'AN DAN HADIS: KAJIAN LITERATUR DAN IMPLEMENTASI DALAM KELUARGA - Asraf Kurnia; Syafruddin Syafruddin; Hendrizal Hendrizal; Heri Effendi; Sartika Fortuna Ihsan (Al-ATHFAL: Jurnal Pendidikan Anak, 2024)
This article discusses the importance of Early Childhood Education (ECE) from the perspective of the Qur'an and Hadith, as well as its implementation in Muslim families. ECE focuses not only on cognitive aspects but also on moral education, faith, and worship. Through the habituation of Islamic values, good role models from parents, and positive communication, holistic education can be achieved. This study also identifies the challenges of modernization that may threaten Islamic ECE values and offers solutions to address these challenges. By integrating formal and informal educational approaches, it is hoped that future generations will grow into individuals with noble character and faith. The conclusion of this article emphasizes that the role of parents as primary educators is crucial in shaping children's character in accordance with Islamic teachings.Keywords: Early Childhood Education; Qur'an and Hadith; Islamic Values.